Preventing the Separation of Urban Humans from Nature: The Impact of Pet and Plant Diversity on Biodiversity Loss Belief - Minh-Hoang Nguyen; Minh-Hieu Thi Nguyen; Ruining Jin; Quang-Loc Nguyen; Viet-Phuong La; Tam-Tri Le; Quan-Hoang Vuong (Urban Science, 2023)
Despite the dependence of human existence on myriad ecosystem services and products, a high proportion of people feel disconnection from nature due to urbanization. This separation appears to have created an increase in the numbers of climate change and biodiversity loss denialists, thereby weakening global efforts to prevent environmental degradation and address environmental issues. The current study employs the reasoning capability of Mindsponge theory and the statistical advantages of Bayesian inference to examine whether access to in-home pet and plant diversity can increase the probability of biodiversity loss belief among urban residents. The findings from 535 Vietnamese respondents indicate that, when respondents feel comfortable at home, a higher diversity of pets is associated with a higher likelihood of believing that biodiversity loss is a real and major problem. However, the effect becomes the opposite when the respondents feel uncomfortable at home. Plant diversity has a positive impact on biodiversity loss belief regardless of comfort. Notably, the impact of plant diversity on biodiversity loss belief is more substantial among respondents who feel uncomfortable than those who feel comfortable. Following these findings, we suggest that increasing in-home biodiversity can be a promising way to raise urban residents’ awareness of the occurrence and significance of biodiversity loss, which will subsequently help them build up an eco-surplus culture.